The Role of Marketing Information System (MkIS) to Improve Performance in the Banking Sector of Jordan - Al Khawaldeh, Bashar Issa Ghafel (2010)
The banking sector has always been high information intensive over the years. This has brought the use of Information technology (IT) as a necessity for data storage, modification and retrieval. Information systems (IS) use the provided infrastructure of IT to leverage advantages of IT and to solve many issues that relates to information acquisition. To these end most financial institutions has been using different types of information systems to gain competitive advantage. One of such system is the Marketing information system (MkIS). The purpose of this study is to explore the role of MkIS in the performance of banking sector in Jordan, an emerging modern Arab economy in the Middle East. The present study modifies the technology acceptance model and the organization effectiveness (organization theory) and applies it to usage of MkIS in the Jordanian banks. With the use of MkIS, banks can make notable savings, increase their customer base, increase sales growth and effectively acquire market and customer information. The availability of this information will assist the banks to improve customer service and invariable win the trust of customers and increase customers' patronage. Quite a number of the banks in Jordan make use of information system. But there is no empirical study yet on the use of MkIS in Jordan, neither are there literatures on the role to which MkIS to the performance of the banks. Therefore, a combination of TAM model and organization effectiveness models were used to investigate the influence of MkIS on bank performance. The result of this study which stands as contribution, as it was revealed that there are positive relations to bank performance as hypothesized. The positive association between combination among all independent variables (ease of use, usefulness, attitude, market procedural improvement, employee support, customer knowledge and market responsiveness)were supported.